FORMATION OF AUTOPEDAGOGICAL COMPETENCE IN FUTURE TEACHERS IN THE CONTEXT OF THE MODERN EDUCATIONAL PROCESS - Malika Muminovna Parpiyeva (European Science Publishing, 2024)
This article deals with the problem of the formation of auto-pedagogical competence of future teachers in the context of the modern educational process. The main emphasis is on creating conditions for independent learning, self-development and self-education of students. A comprehensive and systematic approach to this task is being developed, including the development of special educational programs, methods and technologies, as well as the use of modern information and educational technologies and resources. Attention is also focused on the organization of practical training for future teachers and mentoring by experienced professionals.
Keywords: Autopedagogical competence, future teachers, self-education, self-development, educational process, methodology, educational strategy.